Transformasi Nilai Efikasi Diri dalam Penguatan Budaya Mutu Sekolah - Muh. Takdir; Wawan Karsiwan; Nasir Nasir (Universitas Kristen Satya Wacana, 2022)
The aim of this study was to analyse the transformation process of self-efficacy values oriented towards strengthening the quality culture in schools. This study uses a qualitative design with an interactive model approach developed by Joseph A. Maxwell. This research was conducted at several Junior High School (SMP) of Muhammadiyah at Bogor Regency. Sources of data in this study were conducted through interviews, observations, document studies, and Focus Group Discussions (FGD) with research participants, including the Chairman of the Regional Leadership of Muhammadiyah (PDM) Bogor Regency, Chairman of the PDM District Primary and Secondary Educatio, school principals, teachers, staff, students, and representatives of parents/school committees taken purposively according to the needs of the research data. The results of the study show that the transformation of self-efficacy values oriented to a school quality culture can be seen in four indicators, namely the effectiveness of the performance of educators and education, the collaborative spirit of stakeholders, the development of a learning community in schools, and a conducive school climate. Strengthening the value of self-efficacy is not only limited to fulfilling the principle of professionalism, but also based on the religious spirit.